UK ethnic minority healthcare workers’ perspectives on COVID-19 vaccine hesitancy in the UK ethnic minority community: A qualitative study - Sagoe, Dominic; Ogunbode, Charles; Antwi, Philomena; Knizek, Birthe Loa; Awaleh, Zahrah; Dadzie, Ophelia (Frontiers in Psychology, 2022)
Background: The experiences of UK ethnic minority (UKEM) healthcare workers are crucial to ameliorating the disproportionate COVID-19 infection rate and outcomes in the UKEM community. We conducted a qualitative study on UKEM healthcare workers’ perspectives on COVID-19 vaccine hesitancy (CVH) in the UKEM community. Methods: Participants were 15 UKEM healthcare workers (11 females; age range: 26–58 [43.3 ± 9.4] years). Data were collected using individual and joint interviews, and a focus group, and analysed using thematic analysis. Results: We generated three themes: heterogeneity (two subthemes), mistrust (six subthemes), and mitigating (six subthemes). Therein, participants distinguished CVH in the UKEM community in educational attainment and ethnicity. They pointed to the role of mistrust in CVH in the UKEM community. They opined that the mistrust underlying CVH in the UKEM community is rooted in history and religion, conspiracy theories, the speedy development and novelty of the vaccines, post-vaccination complications/side effects, false positive test results, and social media and social support/influence. Participants recommended that interventions targeted at mitigating CVH in the UKEM community need to, in a non-judgmental way, tackle dis/misinformation and provide education, and incorporate UKEM healthcare worker endorsement. They also suggested such interventions be community-oriented, enhance the convenience of vaccination centres and the possibility of vaccine choice, and appreciate that overcoming CVH and accepting vaccination is a gradual process involving personal assessment of risks and benefits. Conclusion: CVH in the UKEM community is a multifaceted phenomenon requiring multicomponent interventions.